(untitled) (Літератури світу: поетика, ментальність і духовність, 2015)
The interpretation of poems «Blue Hussars» and «December Fog» by N. Aseev in the artistic ideology context of the Russian literature Petersburg text and taking into consideration the meanings of Pushkin’s reminiscences in their structure reveals the internal contradictions of Decembrists’ images and lyrical subject, created by the poet, causes semantic multidimensionality of the text.